Cognitive Learning Outcomes of Elementary School Students Through Differentiated Problem-Based Learning - Husna Lailatul Latifa; Sigit Saptono; Barokah Isdaryanti (Universitas Negeri Semarang, 2025)
Learning that focuses solely on one-way knowledge transmission without integrating students into the learning process is one factor contributing to students' low cognitive learning outcomes. Conventional learning encompasses this kind of learning. Since every student learns differently, the current application of the Merdeka Curriculum's tenets is not in line with the use of conventional teaching methods. The purpose of this study is to investigate how the use of a differentiated Problem-Based Learning paradigm can improve students' cognitive learning outcomes in science. This study uses Nonequivalent Control Group Design and is quantitative in nature. The study's sample comprised 28 fourth-grade children from SDN Ngemplak Simongan 01 and 28 students from SDN Manyaran 03. The N-Gain test findings, which show that the experimental group received an average score of 0.71 while the control group received an average score of 0.55, provide evidence of this. Furthermore, the independent sample t-test used for hypothesis testing produced a significant value of 0.000<0.05, which resulted in the rejection of H0. This suggests that, in comparison to children who received conventional instruction, the cognitive learning outcomes of students taught utilizing the differentiated PBL paradigm demonstrated a high degree of progress and a significant difference.